Influence of an Indirect Precursor on Podophyllotoxin Accumulation in Cell Suspension Cultures of Podophyllum hexandrum - Majumder, Anrini (Plant Tissue Culture and Biotechnology, 2013)
Podophyllum hexandrum is an endangered, commercial source of a naturally occurring lignan podophyllotoxin, which is a precursor of potent anticancer drugs. Cell suspension cultures were established using four-year-old cell line RC4 of P. hexandrum in liquid P1 medium [half strength B5 basal medium supplemented with 1% (w/v) sucrose, 2,4-D (1 mg/l), GA3 (1 mg/l) and BA (0.1 mg/l)]. The effect of different concentrations (100, 250 and 500 mg/l) of tryptophan, an indirect precursor of lignan biosynthesis, was studied on cell suspension cultures. Cultures accumulated 2.7 times more podophyllotoxin than untreated control cultures when treated with 250 mg/l tryptophan. Biomass yield was, however not improved following the addition of tryptophan. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14207 Plant Tissue Cult. & Biotech. 22(2): 171-177, 2012 (December)